2012
DOI: 10.1073/pnas.1213449109
|View full text |Cite
|
Sign up to set email alerts
|

Sex, prions, and plasmids in yeast

Abstract: Even deadly prions may be widespread in nature if they spread by infection faster than they kill off their hosts. The yeast prions [PSI+] and [URE3] (amyloids of Sup35p and Ure2p) were not found in 70 wild strains, while [PIN+] (amyloid of Rnq1p) was found in ∼16% of the same population. Yeast prion infection occurs only by mating, balancing the detrimental effects of carrying the prion. We estimated the frequency of outcross mating as about 1% of mitotic doublings from the known detriment of carrying the 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
84
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 70 publications
1
84
0
Order By: Relevance
“…7). Amyloids have also been identified in lower eukaryotes such as the budding yeast Saccharomyces cerevisiae, where they have been proposed to be pathological (8,9). This, however, is controversial, and others have suggested that S. cerevisiae may use amyloids to generate phenotypic diversity, thus allowing it to adapt to environmental stress (10,11).…”
mentioning
confidence: 99%
“…7). Amyloids have also been identified in lower eukaryotes such as the budding yeast Saccharomyces cerevisiae, where they have been proposed to be pathological (8,9). This, however, is controversial, and others have suggested that S. cerevisiae may use amyloids to generate phenotypic diversity, thus allowing it to adapt to environmental stress (10,11).…”
mentioning
confidence: 99%
“…In support of this hypothesis, it was reported that severe stress conditions increased the rate of de novo [PSI+] generation, 25 although we could not independently confirm this observation. 28 If this hypothesis is true, prions should arise and be stabilized under stress conditions. TAPI offers an opportunity to test whether yeast strains subjected to selective pressures could generate specific SDS-resistant protein profiles.…”
Section: Application Of Tapi For New Amyloid Discoverymentioning
confidence: 99%
“…While beneficial phenotypes of [PSI+] formation have been reported (Eaglestone et al 1999;True et al 2004), they have not been reproducible (True et al 2004;Namy et al 2008), even using the identical strains. Moreover, the common occurrence of lethal and near-lethal variants of [PSI+] (McGlinchey et al 2011) and the rare occurrence of [PSI+] in the wild (Chernoff et al 2000;Resende et al 2003;Nakayashiki et al 2005;Halfmann et al 2012) implies that [PSI+] is generally detrimental to its host (Nakayashiki et al 2005;Masel and Griswold 2009;Kelly et al 2012).…”
mentioning
confidence: 99%